Considerations for Treating Corona Virus (Sars-Cov-2) Infection with Passive Immunotherapy - Abraham Karpas; Douglas Bainbridge; Stephen Ash (Substantia, 2020)
The corona viruses are transient RNA viruses; once an infected individual recovers he or she becomes virus-free and immune. One could expect that in SARS-Covid-19 also, infected individuals who recover will have developed some form of protective immunity. Very little is yet known about its development, when and for how long it might last, and though it is very likely to involve virus-neutralising antibodies, to what extent it might depend on the appearance of such antibodies. However in a recent report 10 very advanced corona patients were treated with a single 200 ml dose of plasma obtained from individuals recovered from the infection. There was impressive clinical improvement.